Endocrine secrets - McDermott, Michael T. (Hanley & Belfus, 1995)
This informative text is part of the "Secrets" series, and addresses many important topics in the fields of endocrinology and metabolism using a question-and-answer format. Topics covered include diabetes mellitus, adrenal problems and interesting facts and figures.